What induces firms to license foreign technologies? International survey evidence. (17th July 2019) - Dohse, Dirk; Goel, Rajeev K.; Nelson, Michael A.
Abstract : The paper provides insights into drivers of foreign technology licensing from the licensee's perspective, using data across 114 nations. Technology licensing enables licensees to access proven technologies without development delays, although licensors might deny licenses for strategic reasons. Results show that firms with own R&D are more likely to license foreign technologies, as are larger firms and firms in the nations' main business cities. However, the macroeconomic and institutional environment matters as well: domestic interest rates, informal sector competition, and the literacy of a country's labor force all impact foreign technology licensing. Some implications for technology policy are discussed.